2002
DOI: 10.1002/ccd.10394
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter occlusion of ruptured sinus of valsalva aneurysm: Innovative use of available technology

Abstract: A 9-year-old boy was found to have ruptured sinus of Valsalva aneurysm (RSVA) and aortic coarctation. Following relief of aortic coarctation by balloon angioplasty, transcatheter coil occlusion of the RSVA was performed successfully under transesophageal echocardiographic and fluoroscopic monitoring; bioptome-assisted delivery of 0.052" Gianturco coil was undertaken via a 7 Fr sheath stabilized by an 0.035" guidewire passing through the RSVA and the sheath. This report details the technique of occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 21 publications
(14 reference statements)
0
28
0
Order By: Relevance
“…Because no devices have been specially designed for these defects, several devices, such as the Gianturco coil, 14 Amplatzer AO, aorta; AVB, atrioventricular block; IRBBB, incomplete right bundle branch block; NYHA, New York Heart Association; NCS, noncoronary sinus; PA, pulmonary artery; RA, right atrium; RCS, right coronary sinus; RV, right ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…Because no devices have been specially designed for these defects, several devices, such as the Gianturco coil, 14 Amplatzer AO, aorta; AVB, atrioventricular block; IRBBB, incomplete right bundle branch block; NYHA, New York Heart Association; NCS, noncoronary sinus; PA, pulmonary artery; RA, right atrium; RCS, right coronary sinus; RV, right ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…14 Rao et al reported the use of a Gianturco coil 0.052" with a bioptome assisted technique to close RSVA in one. 15 Fedson et al reported use of the Amplatzer duct occluder in closing the RSVA in a patient in whom the retention disc was deployed in the aneurysm and the rest of the device to the drainage site. 16 Arora et al reported a series of 8 patients with RSVA, who underwent transcatheter closure with Amplatzer duct occluder in 5, an Amplatzer septal occluder in 1 and a Rashkind umbrella device in 2.…”
Section: Discussionmentioning
confidence: 99%
“…8 Advances in cardiac catheterisation technology have resulted in a wide range of devices and coils which can be used to close a RSVA. [9][10][11][12][13][14][15] Retrograde and combined minimally invasive surgery hybrid approaches have been described in certain cases. 16,17 Based on a retrospective review of 257 patients, Guo et al proposed a new system of simple surgical classification for right-sided defects according to rupture site.…”
Section: Discussionmentioning
confidence: 99%